The Zika Virus Infection in Pregnancy: Review and Implications for Research and Care of Women and Infants in Affected Areas - Zorrilla, Carmen D.; Rivera-Viñas, Juana I.; De La Vega-Pujols, Alberto; Garcia-Garcia, Inés; Rabionet, Silvia E.; Mosquera, Ana M. (Puerto Rico Health Sciences Journal, 2018)
The world has encountered a new and serious epidemic which has disproportionately affected fetuses and infants. What makes the Zika virus (ZIKV) epidemic such a threat in our times, is that a whole generation can be affected by birth defects caused by a seemingly innocuous maternal infection, which in most cases go unnoticed and undiagnosed. Spreading to over 80 countries and affecting millions, it is associated with severe birth defects known as congenital Zika syndrome (CZS), which include fetal brain development abnormalities (microcephaly and brain calcifications), retinal abnormalities, and contractures and hypertonia of the extremities. Testing strategies are challenging because of the lack of symptoms and cross reactivity with other viral infections. Obstetrical complications include fetal loss and the need for an emergency cesarean delivery. The rate of CZS has been described as ranging from 5 to 6% among cohorts in the US, reaching 11% for 1st trimester exposure. Prolonged viremia during pregnancy has been documented in a few cases, reaching 89 days after the onset of symptoms in one case and 109 days after such onset in another. If the ZIKV can infect, multiply in, and persist in diverse placental cells, then movement across the placenta, the fetal brain, and the maternal peripheral blood is possible. There is a sense of urgency, and we need safe and effective vaccines and treatments, particularly for pregnant women. If we do not expand testing and develop methods for early diagnosis and treatment, thousands of infants will be exposed to a neurotropic virus that causes severe birth defects and that could also affect the lives of those who form the next generation.